Corpus-based Critical Translation Studies: Research Areas and Approaches - Hu, Kaibao; Li, Xiaoqian (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
This paper discusses the origin, features, research areas, and approaches, as well as the implications, of corpus-based critical translation studies (CCTS), with a view to establishing a theoretical framework. It is argued that CCTS, born of corpus-based translation studies and critical translation studies, will serve to unveil ideological factors behind the translated texts and the process involved. The birth of CCTS has not only revolutionized the methodology of critical translation studies, but has also broadened its scope.